2003
DOI: 10.1097/00005373-200303000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Acute Complications Associated with Greenfield Filter Insertion in High-Risk Trauma Patients

Abstract: Our data indicate that complications of GF insertion for prophylaxis against PE from DVT complicating trauma patients continue to be negligible. In addition, the incidence of insertion-site thrombosis may be lower than expected. Moreover, femoral AVF is a rare complication of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…[1][2][3][4] RFs offer a similar prophylactic benefit without the long-term risks of PFs, and multiple studies have demonstrated that RFs may be inserted and retrieved with low rates of significant complications. 12,[25][26][27][28] At our institution, the perceived change in the risk-tobenefit ratio of filter placement presented by the availability of a RF was associated with a threefold increase in our rate of filter placement in trauma patients. We found a higher rate of DVT in Group II.…”
Section: Retrievable Vena Cava Filters For Trauma Patientsmentioning
confidence: 87%
See 1 more Smart Citation
“…[1][2][3][4] RFs offer a similar prophylactic benefit without the long-term risks of PFs, and multiple studies have demonstrated that RFs may be inserted and retrieved with low rates of significant complications. 12,[25][26][27][28] At our institution, the perceived change in the risk-tobenefit ratio of filter placement presented by the availability of a RF was associated with a threefold increase in our rate of filter placement in trauma patients. We found a higher rate of DVT in Group II.…”
Section: Retrievable Vena Cava Filters For Trauma Patientsmentioning
confidence: 87%
“…4,5,17,20,22,25,30 -32 The 2.5% rate of major filter-related complications in the current study confirms the experience of other centers describing low complication rates from RF placement and retrieval. 12,[25][26][27][28] Although low complication rates and few long-term sequelae make RFs ideal in many regards, the extension of established indications for IVC filter placement in the trauma population should be based on evidence that more liberal filter placement may lead to a decrease in the rate of PE. The 0.2% rate of clinically detected PE in our trauma population was not reduced by our more aggressive IVC filter placement strategy.…”
Section: Retrievable Vena Cava Filters For Trauma Patientsmentioning
confidence: 99%
“…A subset analysis was performed of the 310 patients who had undergone R-IVCF placement for prophylactic indications, which included at least one of the following: lowerextremity fracture (123); closed head injury (113); pelvic fracture (108); need for spine operation (88); upper-extremity fracture (35); and solid organ abdominal injury (33). Ninetyfive (31%) had at least one lower-extremity venous duplex study performed after placement (45.6 Ϯ 53.2 days).…”
Section: Underwent Placement Of a Retrievable Filtermentioning
confidence: 99%
“…IVC filters have been shown to prevent PE, but are associated with their own risks [7][8]. These include IVC erosion, perforation, migration, filter infection, filter occlusion, formation of thrombi proximal to the filter, insertion site trauma, and DVT [9][10][11]. The ideal intervention would be a temporary IVC filter that is removed perioperatively, once the patientÕs risk of VTE has diminished.…”
mentioning
confidence: 99%